The economics of John Kenneth Galbraith : introduction, persuasion, and rehabilitation - Dunn, Stephen P. (Cambridge : Cambridge University Press, 2011)
The recent financial crisis has once again seen John Kenneth Galbraith return to the bestseller lists. Yet, despite the continued popular success of his works, Galbraith's contribution to economic theory is rarely recognized by today's economists. This book redresses the balance by providing an introductory and sympathetic discussion of Galbraith's theoretical contributions, introducing the reader to his economics and his broader vision of the economic process. The book highlights and explains key features of Galbraith's economic thought, including his penetrating critique of society, his distinctive methodology, his specific brand of Keynesianism and his original - but largely ignored - contribution to the theory of the firm. It also presents, for the first time, a detailed examination of Galbraith's monetary economics and revisits his analysis of financial euphoria. This unique work seeks to rehabilitate Galbraith's contribution, setting out several directions for possible future research in the Galbraithian tradition.
1. The eclipse of the new industrial state? -- 2. A life in our times -- 3. The economics of John Kenneth Galbraith -- 4. The methodology of John Keneth Galbraith -- 5. The general theory of advanced development -- 6. Why people are poor -- 7. Uncertainty and the modern corporation -- 8. A theory of the multinational corporation -- 9. The management of specific demand -- 10. Money and the real world -- 11. A man for our times -- 12. The origins of the Galbraithian system: talking to John Keneth Galbraith.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Galbraith, John Kenneth, -- 1908-2006.; Economics -- United States